Using Extractive Revenues for Sustainable Development: Policy Guidance for Resource-rich Countries (OECD Development Policy Tools, 2019)
Transforming natural finite assets into human, social and physical capital is a key challenge for natural resource-rich countries. This report distils related lessons from the OECD Policy Dialogue on Natural Resource-based Development on natural resource revenue management and spending for sustainable development. This includes a guide on how natural resource-rich countries can ensure budget sustainability to support consistent spending over time. Further analysis focuses on the management of spending versus saving and the effectiveness of different spending mechanisms for sustainable development, making recommendations to address current challenges.